The Impact of a Short Conservation Education Workshop on Argentinean Students’ Knowledge about and Attitudes towards Species - Nates, Juliana (2012)
This study investigated the impact of a one-day conservation education workshop on knowledge about and attitudes towards species of 88 students from Valle Fértil, Argentina. Immediately before and after the workshop and one year later, students (aged 12 to 16) had to identify native and introduced exotic plant and animal species as well as artificial ones ("Simpsons") on flashcards, to point out those "species" they considered most beautiful and useful, and to name adaptations of local species to arid conditions. Immediately after the workshop, students strongly increased their knowledge about plants and adaptations. One year later, this was still the case for those plant species students had been already somewhat familiar with in the pretest. The workshop hardly changed attitudes.